2015
DOI: 10.14382/epitoanyag-jsbcm.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additives on the Rheological Properties of Fast Curing Epoxy Resins

Abstract: rapid resin transfer molding (rtm) process is suitable for high-throughput manufacturing of complex-shaped composite parts. ideally the epoxy system should exhibit low viscosity and long gel time at room temperature for quick mold filling, and very fast curing once the resin is inside the heated mold. the present research was performed on different epoxy formulations by varying the concentrations of diluent and catalyst. rheological studies were carried out to measure the flow viscosity and to determine the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Figure 8 shows the dynamic storage modulus (G ) and loss modulus (G") versus temperature during heating at a heating rate of 2 • C/min. These rheograms confirm that curing processes are time-and temperature-dependent [18,29]. Although the shapes of the curves obtained for elastic and viscous modulus are similar for all formulations, the curing reactions start at considerably different temperatures (i.e., times).…”
Section: Rheological Characteristicssupporting
confidence: 67%
See 3 more Smart Citations
“…Figure 8 shows the dynamic storage modulus (G ) and loss modulus (G") versus temperature during heating at a heating rate of 2 • C/min. These rheograms confirm that curing processes are time-and temperature-dependent [18,29]. Although the shapes of the curves obtained for elastic and viscous modulus are similar for all formulations, the curing reactions start at considerably different temperatures (i.e., times).…”
Section: Rheological Characteristicssupporting
confidence: 67%
“…Time-dependent FT-IR absorbance measurements during temperature treatment of coatings (Figures 4-6) enables insight into the crosslinking by observation of decreasing intensity of the epoxy mode at 915 cm −1 [28]. Rheology (Figures 7 and 8), on the other hand, gives quite a piece of information on changes in consistency during the transformation of the formulation into a crosslinked structure [18,29]. When the obtained results are observed in parallel experiments, designed to approach to the same conditions as much as possible, they can throw light to the curing processes that lead to the formation of highly crosslinked protective coatings.…”
Section: Characteristics Of Formulations and Curing Processmentioning
confidence: 99%
See 2 more Smart Citations
“…All samples were exposed to white light and the storage modulus recorded. The storage modulus increases with time and in most cases (AI, AII, AIII, BI, BII and CI) reaches a plateau indicating no further significant growth of elastic structures due to the crosslinking 33 . It was observed that the plateau region of the storage modulus was dependent on the polymerisation solvent used (Fig.…”
Section: Photo-induced Curingmentioning
confidence: 96%